Pengaruh Kualitas Institusi, Pengeluaran Pemerintah, dan Foreign Direct Investment terhadap Pertumbuhan Ekonomi - Anastia Widianatasari; Evi Yulia Purwanti (Jurusan Ilmu Ekonomi dan Studi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Lambung, 2021)
Economic growth in developing countries is prone to global economic fluctuations such as the 2008 financial crisis. This study has two objectives. First, analyze institutional quality, government expenditure, and foreign direct investment on economic growth. Second, analyze institutional quality and government expenditure on economic development through FDI. This study uses two analytical methods: panel data regression and the common effect model (CEM) approach and path analysis. The objects used in the research were nine developing countries in Asia in 2012-2019. The finding revealed that three variables of institutional quality have a significant effect on economic growth. There is a negative effect of voice and accountability, a positive effect of political stability, the absence of violence/terrorism, and the regulatory quality. Meanwhile, control of corruption does not affect economic growth. In addition, government expenditure has no significant impact on economic growth, whereas foreign direct investment has a significant negative effect. Furthermore, all institutional quality variables have no significant effect on economic development through FDI, but government expenditure has a significant negative impact on economic growth via FDI. Governments can carry out regulatory reforms, review government spending allocations, and control FDI inflows to stimulate economic growth in developing countries.